Supervisory Function and Corporate Tax Policy: Gender Analysis - Deden Tarmidi; Agustin Fadjarenie; Noor Hazlina Ahmad; Erna Sofriana Imaningsih; Sri Marti Pramudena (The Indonesian Accounting Review, 2025)
This study analyses the role of independent commissioners and audit committees in carrying out their supervisory functions on corporate tax policies taken by internal management, gender analysis on independent commissioners and audit committees is unique to this study where different behaviors of men and women have different impacts on independent commissioners and audit committees in carrying out their supervisory functions. A total of 570-panel data from 2015 to 2021 financial statements of manufacturing companies on the Indonesia Stock Exchange were analyzed, this study found that multi-gender audit committees have a role in encouraging management to comply with tax regulations in the policies taken, as well as female audit committees and male independent commissioners separately. These results provide input for investors who are concerned about entity tax information to choose entities with criteria according to the findings of this study, namely entities that have multi-gender audit committees, entities that have female audit committees only, or entities that have independent commissioners only because the supervisory function carried out is optimal in encouraging tax-compliant entities and entities avoid the risk of tax penalties in the future.